Un quinquenio del proyecto formación de formadores en robótica: La experiencia de un proyecto de extensión universitaria en Costa Rica - Hernández Ruiz, Irene (2020)
This article shows the results and achievements obtained during a five-year period in the project: "Training of Trainers in Robotics in schools in vulnerable areas of Costa Rica", which has aimed to train secondary school teachers in the area of educational robotics so that in turn they can replicate their knowledge with high school youth, both in the greater metropolitan area and in rural areas of Costa Rica. The trained youth have managed to have a recreational and educational space to put programming concepts into practice using the Lego EV3 tool as a means of learning. The project has been developed jointly by the School of Informatics of the National University, the Costa Rican Institute on Drugs and the Ministry of Public Education of Costa Rica.